A Longitudinal Study of Racial Discrimination and Risk for Death Ideation in African American Youth. Issue 1 (3rd May 2016) - Walker, Rheeda; Francis, David; Brody, Gene; Simons, Ronald; Cutrona, Carolyn; Gibbons, Frederick
Abstract : Although multiple studies have found that African Americans commonly experience racial discrimination, available studies have yet to examine how perceived racism might be related to suicide vulnerability in African American youth. The purpose of this study was to examine a framework for how perceived racial discrimination contributes to symptoms of depression and anxiety as well as subsequent suicide ideation and morbid ideation. Data were obtained from 722 African American youth at mean age 10.56 years ( SD = 0.64); a second wave of data was obtained 2 years later. Results revealed both a direct effect and mediated effects of perceived racism on later suicide and morbid ideation. For boys and girls, the effect of perceived racism was mediated by symptoms of depression. However, the association was mediated by anxiety for girls, but not for boys in the current sample. Implications for future research and interventions are discussed.